Agile development of a digital exposure treatment for youth with chronic musculoskeletal pain: protocol of a user-centred design approach and examination of feasibility and preliminary efficacy. Issue 9 (15th September 2022) - Harrison, Lauren E; Webster, Sarah N; Van Orden, Amanda R; Choate, Ellison; Jehl, Nicole; Stinson, Jennifer; Wicksell, Rikard K; Darnall, Beth D; Simons, Laura E
Abstract : Introduction: Chronic pain affects a significant number of children and impacts multiple domains including social, emotional and behavioural functioning, and negatively impacts family functioning. Roughly 5% of youth with chronic pain experience moderate to severe pain-related disability, with pain-related fear and avoidance of activities being identified as substantial barriers to treatment engagement. Evidence supports targeted psychological and physical interventions to address these barriers (eg, graded-exposure treatment), but accessibility to intervention is undermined by a shortage of services outside of urban areas, high treatment-related costs, and long provider waitlists; highlighting the need to develop digitally delivered behavioural intervention, using agile and iterative study designs that support rapid development and timely dissemination. Methods and analysis: This study seeks to develop an effective and scalable intervention for youth with chronic pain and their caregivers. This paper presents a user-centred protocol for the development and refinement of a digital exposure treatment for youth and caregivers, as well as the study design to examine feasibility and preliminary efficacy of the treatment using single-case experimental design (SCED). Assessments include daily diaries, completed from baseline and daily throughout the intervention ( 6 weeks), and at 3-month follow-up, as well as self-report measures completed at baseline, end of intervention and 3-month follow-up. Primary outcomes include treatment satisfaction, treatment expectancy, adherence to daily dairies and functional disability. Secondary outcomes are pain-related fear and avoidance of activities, pain catastrophising and pain acceptance. We will present descriptive and model-based inference analyses, based on SCED reporting guidelines. We will calculate effect sizes for each individual on each outcome. We will examine mean treatment expectancy, credibility and satisfaction scores, and patient drop-out percentage. Ethics and dissemination: This study is approved by the Institutional Review Board at Stanford University (protocol #53323). Findings will be actively disseminated through peer-reviewed journals, conference presentations and social media. Trial registration number: NCT05079984 .